OPTIMIZING PRISONERS' RISK AND NEEDS ASSESSMENT IN PEMATANG SIANTAR CLASS IIA REHABILITATION - Rajagukguk, Binsar Parulian; Equatora, Muhammad Ali; Muhammad, Ali (ANAYASA : Journal of Legal Studies, 2025)
Independence coaching is a form of program implemented by providing work guidance training which is an effort to provide provisions and skills to correctional prisoners while they are serving their sentences which are useful when the prisoners return to the midst of society in providing such guidance, an assessment is carried out where the assessment activities carried out on correctional prisoners aim to collect data and information on correctional prisoners which are then verified and analysed to provide an assessment of the risks and needs of correctional prisoners, its implementation refers to the Minister of Law and Human Rights Regulation number 12 of 2013 concerning risk assessment and assessment of the needs of prisoners, The method used in this research is descriptive method to analyse a research with a case study as a series of activities in obtaining data by presenting the actual situation and explaining the circumstances and conditions of the problem, Optimisation of risk assessment and needs assessment in the independence coaching program at the Pematang Siantar class IIA correctional institution is currently not optimal where its implementation should refer to the Minister of Law and Human Rights Regulation number 12 of 2013 concerning risk assessment and needs assessment of prisoners, this is because in the implementation of risk assessment and needs assessment itself in the Pematang Siantar class IIA correctional institution there are obstacles accompanied by various factors.